Synergistic removal of NO and N2O in low-temperature SCR process with MnOx/Ti based catalyst doped with Ce and V. (1st December 2016) - Niu, Yanqing; Shang, Tong; Hui, Shien; Zhang, Xiaolu; Lei, Yu; Lv, Yuan; Wang, Shui
Graphical Abstract: Highlights: NO removal and N2 O inhibition are achieved in low-temperature SCR with MnOx/Ti catalyst. N2 O mainly originated from direct oxidation of NH3 and reaction of NO and adsorbed NH3 . Reaction of NO and adsorbed NH3 plays a dominate role in N2 O formation at temperature below 240 °C. Doped V promotes Lewis acid sites which effectively restricts N2 O formation. Mn(0.4)Ce(0.1)V(0.01)/Ti ensures high NO conversion efficiency and low N2 O formation. Abstract: Aiming at understanding N2 O formation in a low-temperature SCR process, mechanistic studies regarding the synergistic removal of NO and inhibition of N2 O formation by the addition of Ce and V into MnO x /Ti based catalysts prepared by the sol-gel method were conducted and analyzed by various techniques, including BET, XRD, XPS, NH3 -TPD, and FTIR. The results show that the addition of Ce raises the NO conversion efficiency and shifts the high performance region toward the low temperature range, while the addition of V generates less N2 O. As an optimal formula, Mn(0.4)Ce(0.1)V(0.01)/Ti ensures a high NO conversion efficiency and low N2 O formation. N2 O mainly originates from (1) the direct oxidation of NH3 with O2 and (2) the reaction of NO and adsorbed NH3 in the low-temperature SCR process. The latter plays a dominant role at temperatures below 240 °C. The strong redox properties on the MnO x /Ti catalyst surface result in a high NO conversion efficiency and generates numerous NH(ads) species that cause N2 O formation. The slight addition of V promotes the formation of acid by bringing Lewis acid sites to the catalyst surface and effectively restricts N2 O formation. Lewis acid sites have a positive function in maintaining a high NO conversion and inhibiting N2 O formation compared to Brønsted acid sites. In addition, the well-dispersed V on the surface of Mn(0.4)Ce(0.1)V(0.01)/Ti results in improved textural properties, more lattice oxygen and less labile oxygen, as well as comparable Mn 4+ /Mn 3+, which also improves the catalyst performance at low temperature.